Longitudinal Weight Loss Patterns and their Behavioral and Demographic Associations. Issue 1 (30th September 2015) - Szabo-Reed, Amanda N; Lee, Jaehoon; Ptomey, Lauren; Willis, Erik; Schubert, Matt; Washburn, Richard; Donnelly, Joseph E.
Abstract: Background: Identification of weight change patterns may allow tailored interventions to improve long-term weight loss. Purpose: To identify patterns of weight change over 18 months, and assess participant characteristics and intervention adherence factors associated with weight change patterns in a sample of 359 overweight/obese adults. Methods: Weight loss (0–6 months) was achieved with reduced energy intake and increased physical activity (PA). Maintenance (7–18 months) provided adequate energy to maintain weight and continued PA. Results: Latent profile analysis identified three weight change profiles. During weight loss/maintenance, participants in profiles 2 and 3 (18-month weight loss ∼14 %) attended more behavioral sessions and performed more PA compared with profile 1 (18-month weight loss <1 %). Self-efficacy for both weight management and exercise barriers were higher in profiles 2 and 3 compared with profile 1 following weight loss and during maintenance. Conclusion: Weight change patterns can be identified and are associated with both participant characteristics and intervention adherence.